Controllable degradable janus silica nanoparticles for oil displacement and application thereof
Patent Information
- Application Number
- CN202410914144.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-09
AI Technical Summary
目前纳米驱油剂主要对SiO2表面改性达到功能化目的,但常规改性SiO2传驱油剂在高温高盐环境下分散性差,驱油效果有限,且常规SiO2稳定性强,在地层中不易降解,随着持续注入,存在堵塞地层孔隙的风险,从而对储层造成不可逆损害
[0013]本发明基于多元醇桥段及氨酯键的可降解性质及Janus粒子的两亲性、高比表面积等特性,与常规改性纳米SiO2相比,本发明驱油剂能有效降低油水界面张力,同时具备可控降解能力,在提高原油采收率方面具有更显著的优势。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a controllable degradable Janus-type silica nanoparticle for oil displacement and its application, belonging to the field of oilfield chemical enhanced oil recovery. Background Technology
[0002] As reservoir conditions become increasingly demanding, conventional enhanced oil recovery (EOR) systems struggle to address challenges such as high water cut, high salinity, ultra-low permeability, and dispersed residual oil in reservoirs. Therefore, developing new materials and technologies to enhance oil recovery is crucial for resolving the energy supply-demand imbalance.
[0003] Nanomaterials possess characteristics such as large specific surface area and high surface energy, which can reduce the interfacial tension between oil and water, thereby enabling the stripping of crude oil from the rock surface and attracting widespread attention in oilfield development. Currently, nano-displacement agents mainly achieve functionalization through surface modification of SiO2. However, conventional modified SiO2 displacement agents exhibit poor dispersibility under high temperature and high salinity environments, resulting in limited oil displacement effects. Furthermore, conventional SiO2 exhibits strong stability and is not easily degraded in the formation. With continuous injection, there is a risk of clogging formation pores, leading to irreversible damage to the reservoir.
[0004] Amphiphilic Janus nanoparticles possess both oleophilic and hydrophilic properties, small particle size, low adsorption capacity, high specific surface area, and the ability to significantly reduce oil-water interfacial tension. Furthermore, they can overcome the disordered transport of Brownianu motion to achieve directional movement, demonstrating significant advantages in enhancing oil recovery. In addition, preparing SiO2 nanoparticles from organosilicon molecules with degradable bridging segments can impart biodegradable properties to nano-SiO2, thereby addressing risks such as formation blockage and providing new ideas and methods for oil displacement in complex reservoirs. Summary of the Invention
[0005] The purpose of this invention is to provide a controllable degradable Janus nano-SiO2 oil displacement agent that can effectively reduce the oil-water interfacial tension and overcome the disordered migration of Brownianu motion to achieve directional movement, thus exhibiting a more significant advantage in improving oil recovery. Furthermore, this type of oil displacement agent has a tunable conformation, is stable in the medium to long term, and can eventually degrade, thereby avoiding formation pore blockage and damage, achieving safe migration, and simultaneously solving the functionality and dispersibility issues of nanomaterials.
[0006] The controllable degradable Janus nano-SiO2 oil displacement agent provided by the present invention is obtained by sequentially modifying the treated degradable nano-SiO2 core material with a hydrophobic modifier and a hydrophilic modifier. The processing steps include coating the biodegradable nano-SiO2 core material with polymethyl methacrylate and oxygen plasma etching. The structural formula of the controllable degradable Janus nano-SiO2 oil displacement agent is shown in (I):
[0007] (I) In the formula, A represents the biodegradable nano-SiO2 core, R1 represents a hydrophobic group, including but not limited to long-chain alkyl and aromatic groups, n represents the number of "-CH2-" groups, and R2 represents a hydrophilic group, including but not limited to amino and urea groups. The controllable degradable Janus nano-SiO2 oil displacement agent has a particle size of 40nm~200nm, with an average of 80~140nm; The oxygen plasma etching time is 10~100s.
[0008] In this invention, the hydrophobic modifier is an alkylsilane coupling agent or an aromatic silane coupling agent, including but not limited to n-octyltriethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane and benzyltriethoxysilane; The amount of the hydrophobic modifier is 30% to 80% of the mass of the degradable organosilicon bridge segment in the degradable nano-SiO2 core material; The modification time using the hydrophobic modifier is 4-6 hours, and it is carried out under reflux.
[0009] In this invention, the hydrophilic modifier is an aminohydrosilane coupling agent, including but not limited to γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-ureapropyltriethoxysilane and γ-(β-aminoethyl)aminopropyltrimethoxysilane; The amount of the hydrophilic modifier is 10% to 50% of the mass of the degradable organosilicon bridge segment in the degradable nano-SiO2 core material; The modification time using the hydrophilic modifier is 4-6 hours, and it is carried out under reflux.
[0010] In this invention, the biodegradable nano-SiO2 core material is prepared by the Stober method from organosilicon molecules with biodegradable bridging segments and tetraethyl orthosilicate. The conditions for the Stobber method are as follows: The dispersion used is an alcohol-water mixture, wherein the volume ratio of alcohol to water is 10~5:0~5, and the amount of water is not zero; The mass ratio of the organosilicon molecule with the degradable bridging segment to the tetraethyl orthosilicate is 1:4~99; The mass fraction of the degradable bridging organosilicon molecules and tetraethyl orthosilicate in the reaction system is 1%~10%; The reaction temperature of the Stober process is 25℃~60℃.
[0011] In this invention, the organosilicon molecule with degradable bridging segments is obtained by an addition reaction of a polyol and propyltriethoxysilane isocyanate; The structural formula of the organosilicon molecule with degradable bridging segments is shown below:
[0012] In the formula, x represents a polyol structural segment with different bridging segments, and the carbon chain length is usually between 2 and 10. The polyols include, but are not limited to, hexahexyl alcohol, 1,2-ethylene glycol, glycerol, butanetyl alcohol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, xylitol, pentaerythritol, and dipentaerythritol. The specific steps are as follows: The polyol and dimethylformamide are added to a round-bottom flask, along with a small amount of triethylamine. The mixture is thoroughly dispersed, and an appropriate amount of propyltriethoxysilane is added dropwise through a dropping funnel at 0°C. After the addition is complete, the mixture is stirred at room temperature. The reaction solution is concentrated under reduced pressure to obtain an oily liquid, yielding the product.
[0013] Based on the degradable properties of polyol bridge segments and urethane bonds, as well as the amphiphilicity and high specific surface area of Janus particles, this invention provides an oil displacement agent that can effectively reduce the oil-water interfacial tension and has controllable degradation capabilities compared to conventional modified nano-SiO2, thus offering a more significant advantage in improving crude oil recovery. Attached Figure Description
[0014] Figure 1 The dispersion stability results are for the controllable degradable Janus nanoparticle oil displacement agent DEG-5%-30s@HTES@TESPU prepared in Example 2.
[0015] Figure 2 The interfacial tension of the controllable degradable Janus nanoparticle oil displacement agent DEG-5%-30s@HTES@TESPU prepared in Example 2.
[0016] Figure 3 The oil displacement effect of the controllable degradable Janus nanoparticle oil displacement agent DEG-5%-30s@HTES@TESPU prepared in Example 2 is shown.
[0017] Figure 4 The demulsification results are for the controllable degradable Janus nanoparticle oil displacement agent DEG-5%-30s@HTES@TESPU prepared in Example 2. Detailed Implementation
[0018] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0019] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0020] The reagents used in the following examples, including propyltriethoxysilane isocyanate (IPTS), hexanediol, 1,2-ethylene glycol, glycerol, butanediol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, xylitol, pentaerythritol, dipentaerythritol, triethylamine, anhydrous ethanol, hydroxylamine aqueous solution, n-octyltriethoxysilane (OTES), dodecyltriethoxysilane (DTES), hexadecyltriethoxysilane (HTES), benzyltriethoxysilane, γ-aminopropyltriethoxysilane (APTES), γ-aminopropyltrimethoxysilane (WD-56), γ-ureapropyltriethoxysilane (TESPU), γ-(β-aminoethyl)aminopropyltrimethoxysilane (AEAPTMS), acetone, and various inorganic salts, were all purchased from Shanghai Aladdin Chemical Reagent Factory.
[0021] Deionized water is prepared using the Milli-Q ultrapure water system.
[0022] The total mineralization of the mineralized water used in the experiment was 32179 mg / L, and the main ion content (mg / L) was Na. + : 10052.08, K + 105.95, Mg 2+ : 1172.08, Ca 2+ 366.88, Cl - : 17588.09, SO4 2- 2691.00, HCO3 - : 153.25.
[0023] To more clearly illustrate the purpose and technical solution of this invention, the following embodiments are provided to further explain the invention, but do not limit the scope of the invention.
[0024] Example 1: Preparation of Janus nano-SiO2 oil displacement agent modified with n-octyltriethoxysilane / aminopropyltriethoxysilane (1) Preparation of organosilicon molecules with degradable bridging segments (taking butanetetraol as an example) 10 g (0.08 mol) of butanethylenetetrol and 100 mL of dimethylformamide were added to a 500 mL round-bottom flask, along with a small amount of triethylamine. The mixture was thoroughly dispersed, and 40 g (0.2 mol) of propyltriethoxysilane isocyanate was slowly added dropwise through a dropping funnel at 0 °C. After the addition was complete, the mixture was stirred at room temperature for 24 h. The reaction solution was concentrated under reduced pressure to obtain an oily liquid with the molecular structure shown in formula (II).
[0025]
[0026] (II) (2) Preparation of biodegradable nano-SiO2 cores 340g of anhydrous ethanol and 40g of distilled water were thoroughly mixed, and hydroxylamine solution was added to adjust the pH. The mixture was heated to 45℃, and 2g of tetraethyl orthosilicate was slowly added dropwise. The reaction solution was vigorously stirred at high speed for 45 minutes to obtain a SiO2 seed solution. Subsequently, 0.4g of organosilicon molecules with degradable bridging segments and 17.6g of tetraethyl orthosilicate were added dropwise using a dropping funnel, and the reaction was continued at 45℃ for 4 hours. After high-speed centrifugation and filtration, the solution was repeatedly washed with distilled water and dried to obtain a biodegradable nano-SiO2 core material, denoted as BTA-2%, meaning that the organosilicon molecules with degradable bridging segments accounted for 2% of the total mass of the feed. Similarly, biodegradable nano-SiO2 core materials labeled BTA-1%, BTA-5%, BTA-10%, and BTA-20% were synthesized following the above steps.
[0027] (3) Preparation of monofunctionalized biodegradable Janus nano-SiO2 particles A biodegradable nano-SiO2 core material coated with polymethyl methacrylate (PMMA) (BTA-2%) was prepared by spin coating, and the PMMA coating was partially removed by oxygen plasma etching for 30 s. Subsequently, 5 g of n-octyltriethoxysilane (OTES) was thoroughly dispersed in 90 g of anhydrous ethanol and 10 g of deionized water, and then added to the partially PMMA-coated biodegradable nano-SiO2 core material after oxygen plasma etching. Triethylamine was added to regulate the catalytic reaction, and the reaction was refluxed at 80 °C for 6 h. After high-speed centrifugation and filtration, the solid product was repeatedly washed with acetone solution to completely remove the PMMA coating, followed by repeated washing with distilled water, high-speed centrifugation, filtration, and drying at 80 °C to obtain hydrophobically modified monofunctional biodegradable Janus nano-SiO2 particles, denoted as BTA-2%-30s@OTES, i.e., BTA-2% etched by oxygen plasma for 30 s and modified with OTES. Similarly, hydrophobically modified monofunctionalized biodegradable Janus nano-SiO2 particles of BTA-2%-10s@OTES, BTA-2%-50s@OTES, and BTA-2%-80s@OTES were synthesized.
[0028] (4) Preparation of bifunctionalized biodegradable Janus nano-SiO2 particles Hydrophobically modified monofunctional biodegradable Janus nano-SiO2 particles (BTA-2%-30s@OTES) were thoroughly dispersed in 100g anhydrous ethanol. Then, 2g of aminopropyltriethoxysilane (APTES) was thoroughly dispersed in 90g anhydrous ethanol and 10g deionized water and added to the nano-dispersion. Triethylamine was added to adjust the pH of the solution, and the mixture was refluxed at 80℃ for 6h. After high-speed centrifugation, the mixture was filtered, and the filter cake was dried at 80℃. The dried sample was then extracted with acetone using a Soxhlet extractor for 24h. Bifunctional biodegradable Janus nano-SiO2 particles, denoted as BTA-2%-30s@OTES@APTES, were obtained. Similarly, bifunctionalized biodegradable Janus nano-SiO2 particles of BTA-2%-10s@OTES@APTES, BTA-2%-50s@OTES@APTES, and BTA-2%-80s@OTES@APTES were synthesized, and their structures are shown in Figure (IV).
[0029]
[0030] (IV) Example 2: Preparation of Janus nano-SiO2 oil displacement agent modified with hexadecyltriethoxysilane / γ-ureapropyltriethoxysilane (1) Preparation of organosilicon molecules with degradable bridging segments (taking diethylene glycol as an example) 12 g (0.11 mol) of diethylene glycol and 100 mL of dimethylformamide were added to a 500 mL round-bottom flask, along with a small amount of triethylamine. The mixture was thoroughly dispersed, and 50 g (0.2 mol) of propyltriethoxysilane isocyanate was slowly added dropwise through a dropping funnel at 0 °C. After the addition was complete, the mixture was stirred at room temperature for 24 h. The reaction solution was concentrated under reduced pressure to obtain an oily liquid with the molecular structure shown in formula (V).
[0031]
[0032] (V) (2) Preparation of biodegradable nano-SiO2 cores Consistent with the steps in Example 1 (2), the degradable nano-SiO2 core material with degradable bridge segments accounting for 5% of the total mass of feed is denoted as DEG-5%. Similarly, degradable nano-SiO2 core materials denoted as DEG-1%, DEG-2%, DEG-10%, and DEG-20% are synthesized.
[0033] (3) Preparation of monofunctionalized biodegradable Janus nano-SiO2 particles A polymethyl methacrylate (PMMA)-coated biodegradable nano-SiO2 core material (DEG-5%) was prepared by spin coating, and the PMMA coating was partially removed by oxygen plasma etching for 30 s. Subsequently, 5 g of hexadecyltriethoxysilane (HTES) was thoroughly dispersed in 90 g of anhydrous ethanol and 10 g of deionized water, and then added to the partially PMMA-coated biodegradable nano-SiO2 core material after oxygen plasma etching. Triethylamine was added to regulate the catalytic reaction, and the reaction was refluxed at 80 °C for 6 h. After high-speed centrifugation and filtration, the solid product was repeatedly washed with acetone solution to completely remove the PMMA coating, followed by repeated washing with distilled water, high-speed centrifugation, filtration, and drying at 80 °C to obtain hydrophobically modified monofunctional biodegradable Janus nano-SiO2 particles, denoted as DEG-5%-30s@HTES, i.e., DEG-5% etched by oxygen plasma for 30 s and modified with HTES. Similarly, hydrophobically modified monofunctionalized biodegradable Janus nano-SiO2 particles of DEG-5%-10s@HTES, DEG-5%-50s@HTES, and DEG-5%-80s@HTES were synthesized.
[0034] (4) Preparation of bifunctionalized biodegradable Janus nano-SiO2 particles Hydrophobically modified monofunctional biodegradable Janus nano-SiO2 particles (DEG-5%-30s@HTES) were thoroughly dispersed in 100g anhydrous ethanol. Then, 3g of γ-ureapropyltriethoxysilane (TESPU) was thoroughly dispersed in 90g anhydrous ethanol and 10g deionized water and added to the nano-dispersion. Triethylamine was added to adjust the pH of the solution, and the mixture was refluxed at 80℃ for 4h. After high-speed centrifugation, the mixture was filtered, and the filter cake was dried at 80℃. The dried sample was then extracted with acetone using a Soxhlet extractor for 24h. Bifunctional biodegradable Janus nano-SiO2 particles, denoted as DEG-5%-30s@HTES@TESPU, were obtained. Similarly, bifunctionalized biodegradable Janus nano-SiO2 particles of DEG-5%-10s@HTES@TESPU, DEG-5%-50s@HTES@TESPU, and DEG-5%-80s@HTES@TESPU were synthesized, and their structures are shown in Figure (VI).
[0035]
[0036] (VI) Example 3: Preparation of Janus nano-SiO2 oil displacement agent modified with benzyltriethoxysilane / γ-(β-aminoethyl)aminopropyltrimethoxysilane (1) Preparation of organosilicon molecules with degradable bridging segments (taking 1,3-propanediol as an example) 8 g (0.11 mol) of 1,3-propanediol and 100 mL of dimethylformamide were added to a 500 mL round-bottom flask, along with a small amount of triethylamine. The mixture was thoroughly dispersed, and 50 g (0.2 mol) of propyltriethoxysilane isocyanate was slowly added dropwise through a dropping funnel at 0 °C. After the addition was complete, the mixture was stirred at room temperature for 24 h. The reaction solution was concentrated under reduced pressure to obtain an oily liquid with the molecular structure shown in formula (VII).
[0037]
[0038] (VII) (2) Preparation of biodegradable nano-SiO2 cores Consistent with the steps in Example 1 (2), the biodegradable nano-SiO2 core material with degradable bridge segments accounting for 5% of the total mass of feed is denoted as PDE-5%. Similarly, biodegradable nano-SiO2 core materials denoted as PDE-1%, PDE-2%, PDE-10%, and PDE-20% are synthesized.
[0039] (3) Preparation of monofunctionalized biodegradable Janus nano-SiO2 particles A polymethyl methacrylate (PMMA)-coated biodegradable nano-SiO2 core material (PDE-5%) was prepared by spin coating, and the PMMA coating was partially removed by oxygen plasma etching for 30 s. Subsequently, 8 g of benzyltriethoxysilane (BTES) was thoroughly dispersed in 90 g of anhydrous ethanol and 10 g of deionized water, and then added to the partially PMMA-coated biodegradable nano-SiO2 core material after oxygen plasma etching. Triethylamine was added to regulate the catalytic reaction, and the reaction was refluxed at 80 °C for 6 h. After high-speed centrifugation and filtration, the solid product was repeatedly washed with acetone solution to completely remove the PMMA coating, followed by repeated washing with distilled water, high-speed centrifugation, filtration, and drying at 80 °C to obtain hydrophobically modified monofunctional biodegradable Janus nano-SiO2 particles, denoted as PDE-5%-30s@BTES, i.e., PDE-5% etched by oxygen plasma for 30 s and modified with BTES. Similarly, hydrophobically modified monofunctionalized biodegradable Janus nano-SiO2 particles of PDE-5%-10s@BTES, PDE-5%-50s@BTES, and PDE-5%-80s@BTES were synthesized.
[0040] (4) Preparation of bifunctionalized biodegradable Janus nano-SiO2 particles Hydrophobically modified monofunctional biodegradable Janus nano-SiO2 particles (PDE-5%-30s@BTES) were thoroughly dispersed in 100g of anhydrous ethanol. Then, 3g of γ-(β-aminoethyl)aminopropyltrimethoxysilane (AEAPTMS) was thoroughly dispersed in 90g of anhydrous ethanol and 10g of deionized water and added to the nano-dispersion. Triethylamine was added to adjust the pH of the solution, and the mixture was refluxed at 80℃ for 4h. After high-speed centrifugation, the mixture was filtered, and the filter cake was dried at 80℃. The dried sample was then extracted with acetone using a Soxhlet extractor for 24h. Bifunctional biodegradable Janus nano-SiO2 particles, denoted as PDE-5%-30s@BTES@AEAPTMS, were obtained. Similarly, bifunctionalized biodegradable Janus nano-SiO2 particles of PDE-5%-10s@BTES@AEAPTMS, PDE-5%-50s@BTES@AEAPTMS, and PDE-5%-80s@BTES@AEAPTMS were synthesized, and their structures are shown in Figure (VIII).
[0041]
[0042] (VIII) Example 4 The thermal degradation performance of degradable SiO2 core materials with different contents and different degradable organosilicon molecular bridge segments was evaluated. The specific experimental method is as follows: A certain mass of nanomaterials was weighed, soaked in water for a certain time, and then centrifuged at 15000 rpm for 20 min. The centrifuged product was washed four times with ethanol and deionized water, dried, and then the morphology and structure were observed by SEM electron microscopy to determine the degradability. The test results are shown in Table 1. It can be seen that the degradability of nanoparticles increases with the increase of the amount of degradable bridge segments. The stronger the hydrophilicity of the degradable bridge segments, the stronger the water molecule penetration, and the stronger the degradability.
[0043] Table 1. Degradation degree of biodegradable nanoparticles over time
[0044] Example 5 The dispersion stability of the biodegradable Janus nano-SiO2 oil displacement agent can be evaluated by the transmittance of the mineralized water suspension of the nano-oil displacement agent to ultraviolet light. The experiment was conducted using a 752N UV-Vis spectrophotometer (INEAS, China) at a wavelength of 600 nm. The specific experimental method was as follows: dispersants and stabilizers were dissolved in mineralized water; the mother liquor of the biodegradable Janus nano-SiO2 oil displacement agent was diluted with mineralized water to the target concentration; the solution was stored in glass sample bottles at a set temperature and allowed to stand. Every so often, one bottle of solution was taken out, shaken by hand for 30 seconds, and allowed to stand for 6 hours. The absorbance was measured, and the transmittance was calculated. The dispersion stability of the biodegradable Janus nano-SiO2 oil displacement agent prepared in Example 2 is shown in [reference needed]. Figure 1 ,Depend on Figure 1 It can be seen that the biodegradable Janus nano-SiO2 oil displacement agent DEG-5%-30s@HTES@TESPU prepared by the present invention still has good dispersion stability after 90 days at 120℃, and has good temperature and salt resistance.
[0045] Example 6 The interfacial tension of DEG-5%-30s@HTES@TESPU prepared in Example 2 at different concentrations was determined using the pendant drop method. The specific steps are as follows: ① Aspirate the low-density phase liquid using a microsyringe and inject it into the measuring tube to form a suitable droplet. ② Record the droplet length and diameter at different times when steady state is reached, and calculate the interfacial tension value. The results are shown below. Figure 2 As shown.
[0046] The reduction in interfacial tension is a crucial indicator for evaluating the interfacial properties of Janus-modified nano-displacement agents. The initial oil-water interfacial tension was 30.2 mN / m. When the concentration of DEG-5%-30s@HTES@TESPU was 100 mg / L, the interfacial tension decreased to 24.3 mN / m. Furthermore, when the concentration increased to 300 mg / L, the interfacial tension further decreased to 18.5 mN / m. This demonstrates that the Janus-modified nano-displacement agent effectively reduces interfacial tension and exhibits excellent interfacial performance.
[0047] Example 7 The extent of enhanced oil recovery is a crucial indicator for evaluating the oil displacement performance of nano-displacement agents. The test used three heterogeneous core layers with a core length of 4.5 × 4.5 × 30 cm and permeability of 200 / 600 / 1500 mD. The injection volume was 0.3 PV, and the agent concentrations were 300 mg / L (BTA-2%-30s@OTES@APTES), 300 mg / L (DEG-5%-30s@HTES@TESPU), and 300 mg / L (PDE-5%-30s@BTES@AEAPTMS). The test temperature was 120℃, the salinity was 32129 mg / L, and the viscosity of the crude oil used in the experiment was approximately 4 mPa·s. The experiment employed a periodic water injection method, which can be carried out as follows: At 120℃, water was injected at a rate not exceeding 0.5 mL / min to saturate the core, obtain the core pore volume, and calculate the water permeability. Then, aged crude oil was saturated at the target temperature at 0.1 mL / min (10 h), 0.2 mL / min (4 h), and 0.5 mL / min (2 h), and the saturated oil volume was recorded. The core was aged at the target temperature for 72 h, and then water-driven at a flow rate of 1 mL / min until the water cut reached approximately 90%. 0.3 PV of nano-displacing agent was injected, and water-driven again until the water cut exceeded 98%. The results of the enhanced oil recovery experiments are shown in Table 3. The oil displacement experiment results show that the biodegradable Janus nano-SiO2 oil displacement agent achieved an enhanced oil recovery of over 10% in cores with lower permeability. Specifically, the nano-displacing agent DEG-5%-30s@HTES@TESPU prepared in Example 2 achieved an enhanced oil recovery of 14.2%. The oil displacement results are as follows: Figure 3 As shown.
[0048] Table 3. Samples showing increased recovery rate Sample number Water drive recovery rate, % The recovery rate of nano-displacement agent, % Final recovery rate, % Average increase in harvest rate, % BTA-2%-30s@OTES@APTES 19.3 29.6 31.3 12.0 DEG-5%-30s@HTES@TESPU 19.7 31.8 33.9 14.2 PDE-5%-30s@BTES@AEAPTMS 20.5 30.0 30.9 10.4 Example 8 Crude oil recovered through nano-flooding is typically a W / O type emulsion. The ease of demulsification and dehydration determines the subsequent processing steps. To further characterize the demulsification and dehydration process of W / O type crude oil emulsions containing the nano-flooding agent DEG-5%-30s@HTES@TESPU, the following method was used for evaluation: The nano-dispersion was prepared into a 300 mg / L homogeneous dispersion in simulated mineralized water. 18 mL of the dispersion and 42 mL of anhydrous crude oil were measured and placed in a 100 mL beaker. The mixture was sheared for 5 min using a high-speed homogenizing shear emulsifier to obtain a homogeneous W / O type crude oil emulsion with a water content of 30%. Subsequently, a high-frequency / high-voltage pulsed AC electric field was used to perform demulsification and dehydration tests. The experimental results are as follows: Figure 4As shown in the figure. The results show that the W / O type emulsion containing the nano-oil displacement agent DEG-5%-30s@HTES@TESPU is rapidly demulsified under the action of a high-frequency / high-voltage pulsed AC electric field. After 10 s of electric field application, an aggregated aqueous phase region begins to appear in the emulsion. After 60 s of electric field application, a clear oil-water layer can be seen, and the oil-water separation phenomenon is obvious.
[0049] This invention introduces polyol bridging segments into organosilicon molecules and uses these as precursors to prepare biodegradable nano-SiO2 core materials, which are then modified with Janus to impart amphiphilicity. The biodegradability varies with the content and structure of the biodegradable organosilicon bridging segments. The Janus-modified biodegradable nano-SiO2 oil displacement agent prepared in Example 2 achieved a 14.2% increase in oil recovery at DEG-5%-30s@HTES@TESPU, and the resulting W / O emulsion rapidly demulsifies and dehydrates under a high-frequency / high-voltage pulsed AC electric field, demonstrating significant advantages in enhancing oil recovery in high-temperature, high-salinity oilfields.
Claims
1. A controllable degradable Janus nano-SiO2 oil displacement agent, obtained by sequentially modifying treated degradable nano-SiO2 core material with a hydrophobic modifier and a hydrophilic modifier; The processing steps include coating the biodegradable nano-SiO2 core material with polymethyl methacrylate and oxygen plasma etching. The structural formula of the controllable degradable Janus nano-SiO2 oil displacement agent is shown in (I): ; (I) In the formula, A represents the biodegradable nano-SiO2 core, R1 represents a hydrophobic group selected from long-chain alkyl and aromatic groups, n represents the number of "-CH2-" groups, and R2 represents a hydrophilic group selected from amino and urea groups. The hydrophobic modifier is an alkylsilane coupling agent or an aromatic silane coupling agent, selected from n-octyltriethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane and benzyltriethoxysilane; The hydrophilic modifier is an aminohydrosilane coupling agent selected from γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-ureapropyltriethoxysilane. The biodegradable nano-SiO2 core material is prepared by the Stober method from organosilicon molecules with biodegradable bridging segments and tetraethyl orthosilicate. The organosilicon molecule with degradable bridging segments is obtained by an addition reaction of polyol and propyltriethoxysilane isocyanate; The polyol is selected from one of 1,2-ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, and pentaerythritol.
2. The controllable degradable Janus nano-SiO2 oil displacement agent according to claim 1, characterized in that: The oxygen plasma etching time is 10~100s.
3. The controllable degradable Janus nano-SiO2 oil displacement agent according to claim 1 or 2, characterized in that: The amount of the hydrophobic modifier is 30% to 80% of the mass of the degradable organosilicon bridge segment in the degradable nano-SiO2 core material; The modification time using the hydrophobic modifier is 4-6 hours, and it is carried out under reflux.
4. The controllable degradable Janus nano-SiO2 oil displacement agent according to claim 1 or 2, characterized in that: The amount of the hydrophilic modifier is 10% to 50% of the mass of the degradable organosilicon bridge segment in the degradable nano-SiO2 core material; The modification time using the hydrophilic modifier is 4-6 hours, and it is carried out under reflux.
5. The controllable degradable Janus nano-SiO2 oil displacement agent according to claim 1 or 2, characterized in that: The conditions for the Stobber method are as follows: The dispersion used is an alcohol-water mixture, wherein the volume ratio of alcohol to water is 10~5:0~5, and the amount of water is not zero; The mass ratio of the organosilicon molecule with the degradable bridging segment to the tetraethyl orthosilicate is 1:4~99; The mass fraction of the degradable bridging organosilicon molecules and tetraethyl orthosilicate in the reaction system is 1%~10%; The reaction temperature of the Stober process is 25℃~60℃.
6. The application of the controllable degradable Janus nano-SiO2 oil displacement agent according to any one of claims 1-5 in oilfield oil displacement.
Citation Information
Patent Citations
Cyclodextrin-mesoporous silicon multifunctional nano drug loading particle
CN108619528A
Preparation method of pH-responsive degradable hollow mesoporous organosilicon nanoparticle
CN108743951A
